Development of quality control methods of promising anticonvulsant - Sych, Igor; Bevz, Natalia; Sych, Irina; Rakhimova, Maryna; Yaremenko, Vitaliy; Perekhoda, Lina (ScienceRise: Pharmaceutical Science, 2018)
In the previous studies, NUPh scientists proved that the search of potential anticonvulsants among derivatives of 1,3,4-thiadiazole is very perspective [1-3]. At the medicinal chemistry department of NUPh N-(5-ethyl-[1,3,4]-thiadiazole-2-yl)-2-nitrobenzamide was synthesized. This substance demonstrated high anticonvulsive activity on pentylentetrazole model of seizure compared to classic drug «Depakin». The substance is patented and proposed for further preclinical studies. One of the most important stages in the introduction of a new medicinal product or substance into medical practice is the development of quality control techniques. The aim. The aim of this work was to develop methods of identification, determination of impurities and quantitative determination of N- (5-ethyl- [1,3,4] -thiadiazole-2-yl)-2-nitrobenzamide for further application in standardization of the substance. Methods. Chromatographically pure sample of N- (5-ethyl- [1,3,4] -thiadiazole-2-yl) -2-nitrobenzamide, methods of IR, UV and 1H NMR spectroscopy. Results. The physical-chemical properties and spectral characteristics of N-(5-ethyl-[1,3,4]-thiadiazole-2-yl)-2-nitrobenzamide were studied, and chemical identification methods were proposed. The optimal conditions for the determination of the impurities by the method of thin-layer chromatography using the method of internal normalization are selected. The assay for N- (5-ethyl- [1,3,4] -thiadiazol-2-yl) -2-nitrobenzamide was carried out by absorption spectrophotometry in the alcohol solution at the wavelength of 282 nm with the absorption index 631. For application of methods such validation characteristics as robustness, linearity, correctness, stability of analytical solutions, precision, convergence, reproducibility, calculation of uncertainty of samples preparation were studied. Conclusions. The methods of identification of N- (5-ethyl- [1,3,4] -thiadiazol-2-yl) -2-nitrobenzamide with the use of chemical reactions and spectral methods of analysis - IR and UV and 1H NMR spectroscopy have been developed. To determine the concomitant impurities in the substance, the TLC method is recommended. Specific and nonspecific impurities were determined. The method of quantitative determination of substance by absorption spectrophotometry method in the ultraviolet region by the method of specific absorption index have been developed